LB-11. Comparison of Viral Loads in Individuals With or Without Symptoms At Time of COVID-19 Testing Among 32, 480 Residents and Staff of Nursing Homes and Assisted Living Facilities in Massachusetts. (31st December 2020) - Lennon, Niall J; Mina, Michael; Rehm, Heidi L; Hung, Deborah T; Smole, Sandra; Woolley, Ann E; Lander, Eric; Gabriel, Stacey
Abstract: Background: Transmission of COVID-19 from people without symptoms confounds public health containment strategies. Comprehensive cross-sectional screening enables assessment of viral load independent of symptoms, informing transmission risks. We quantified SARS-CoV-2 burden by RT-qPCR from comprehensive screening of nursing homes and assisted living facilities in Massachusetts to inform our ability to detect SARS-CoV-2 in individuals with or without symptoms. Methods: From 4/9/20 to 6/9/20, we tested nasopharyngeal (NP) swabs from 32, 480 unique individuals comprising staff and residents of the majority of nursing homes and assisted living facilities in Massachusetts. Symptomatology at the time of sampling and demographic information were provided by each facility. NP swabs were collected, RNA extracted, and SARS-CoV-2 testing performed by RT-qPCR. We compared cycle thresholds (Ct) with a standard curve to quantify viral loads. Results: The nursing home and assisted living facilities resident cohort (N = 16, 966) was 65% female with mean age 82. The staff cohort (N = 15, 514) was 76% female with mean age 45. In all, 2654 residents (15.5%) and 624 staff (4.1%) tested positive for SARS-CoV-2, including 12.7% of residents and 3.7% of staff without symptoms, compared to 53.1% of residents and 18.2% of staff with symptoms. The Ct distributions for viral probes were very similar between populations with and without symptoms (Fig 1), with a statistically but not meaningfully different mean (ΔCt 0.71 cycles, p = 0.006) and a similar range (12–38 cycles). This similarity persisted across all sub-categories examined (age, race, ethnicity, sex, resident/staff). Figure 1 Conclusion: In a large cohort of individuals screened for SARS-CoV-2 by RT-qPCR, we found strikingly similar viral load distributions in patients with or without symptoms at the time of testing. The size of the study population, including both staff and residents spanning a wide range of ages, provides a comprehensive cross-sectional point prevalence measurement of viral burden. Because the distributions of viral loads are very similar regardless of symptoms, existing testing modalities validated for detection of SARS-CoV-2 RNA in symptomatic patients should perform similarly well in individuals without symptoms at the time of testing. Disclosures: All Authors : No reported disclosures